39 microlectures : in proximity of performance - Goulish, Matthew, 1960- (Routledge, 2000)
39 Microlectures: In Proximity of Performance is a collection of miniature stories, parables, musings and thinkpieces on the nature of reading, writing, art, collaboration, performance, life, death, the universe and everything.